자외선 조사와 병행된 녹차 식이 공급이 무모생쥐의 표피 산도 관련 인자 함량 및 젖산 탈수소 효소의 단백질 발현과 활성에 미치는 영향 - 이보민(Lee, Bomin); 김종례(Kim, Jongyei); 황재성(Hwang, Jaesung); 조윤희(Cho, Yunhi) (Journal of nutrition and health, 2016)
Purpose: Skin pH, an indicator of skin health, is maintained by various organic factors, which include lactate, free amino acid (FAA), and free fatty acid (FFA). As skin ages or with illness, skin pH becomes less acidic, and functional food has been developed to maintain the acidic pH of skin. In this study, we determined the dietary effect of green tea extract (GTE) on skin pH of photo-aged mice, as measured by epidermal levels of lactate, FAA, and FFA. The protein expression and activity of lactate dehydrogenase (LDH), an enzyme of pyruvate reduction for lactate generation, was further determined. Methods: Albino hairless mice were fed a control diet (group UV+) or a diet with 1% GTE (group GTE) in parallel with UV irradiation for 10 weeks. A normal control group was fed a control diet without UV irradiation for 10 weeks (group UV-). Results: Skin pH was higher (less acidic) in group UV+ than in group UV-. In parallel, epidermal levels of lactate and FFA, as well as of LDH protein expression and activity, were reduced in group UV+. Dietary supplementation of GTE (group GTE) reduced skin pH to similar to the level of group UV-, and inversely increased epidermal levels of lactate, LDH protein expression and activity, but not of FFA. Although epidermal levels of FAA were similar in groups UV- and UV+, it was increased in group GTE to a level higher than in group UV-. In further analysis of major FFA, epidermal levels of palmitic acid [16:0], oleic acid [18:1(n-9)], and linoleic acid [18:2(n-6), but not of stearic acid [18:0] in group GTE were similar to or lower than those in group UV+. Conclusion: Dietary GTE normalized skin pH with increased levels of lactate and FAA, as well as with increased protein expression and activity of LDH in the epidermis of UVB irradiated hairless mice. 본 연구에서는 자외선 조사와 함께 녹차 추출물 식이를 10주간 공급한 무모생쥐 (GTE군)의 표피 pH 관련 인자의 함량과 LDH 효소의 단백질 발현 및 활성 변화를 자외선 비조사군 (UV-군) 및 자외선 조사군 (UV+군)과 비교 분석하였으며 결과는 다음과 같다. UV+군의 피부 pH는 UV-군보다 유의적으로 증가한 반면 GTE군의 피부 pH는 UV+군에 비해 감소하였으며 그 감소 정도는 UV-군과 유사하였다. UV+군의 젖산 함량은 UV-군에 비해 현저히 감소한 반면 GTE군의 젖산 함량은 UV+군에 비해 증가하였다. UV+군과 UV-군의 총 유리아미노산 함량은 군간 유사하였으나 GTE군의 총 유리아미노산 함량은 UV-군에 비해 현저히 증가하였다. UV+군 및 GTE군의 총 유리지방산 함량은 군간 차이 없이 모두 UV-군에 비해 감소하였으며, GTE군에서 주요 유리지방산인 PA, OA 및 LA의 개별 함량은 모두 UV-군과 유사하거나 감소하였다. UV+군의 LDH 단백질 발현 및 활성은 UV-군에 비해 유의적으로 감소한 반면, GTE군의 LDH 단백질 발현 및 활성은 모두 UV+군보다 증가하였으며 특히 LDH 활성의 증가 정도는 UV-군과 유사하였다. 결론적으로 자외선 조사와 병행된 녹차 추출물 식이 공급은 LDH 발현 및 활성 증가와 함께 젖산 과 총 유리아미노산 함량을 증가시켰으며 궁극적으로 자외선 조사에 의해 증가된 피부 pH를 정상화시켰다.